Evaluation of Humoral Immunological Profile in Infertile Women after IVF Failure in Baghdad City - Heba Mohammed Abed Al-Tamimi1, Farhan Abood Risan1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: An (in Vitro) Fertilization (IVF), means fertilizing an ovum with a spermatozoon outside the body in a culture dish under controlled culture conditions. And It was taken a principle option to treat infertility, which is define as a disease of the reproductive system can be diagnosis by the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. The cause of infertility may be immunological or genetic. A progress was made an in vitro fertilization (IVF) techniques, However the majority of transferred embryos fail to implant. Morphology embryo scoring is the standard procedure for most IVF centers for choosing the best embryo, but remains limited since even the embryos classified as (top quality) may not implant. The initial investigation on the cause recurrent (in vitro) fertilization failure ignites the attention on the reproductive immunology. The production of antibodies is an immunomodulatory factor that causes failure of embryo implantation, and the most commonly studied antibodies in women with implantation failure after IVF procedure , include antiphospholipid (aPL), antisperm antibodies (ASA), and antinuclear antibodies (ANA).Objectives: The aim of this study is to determine the immunological aspects of patients after IVF failure, such as ; antiphospholipid antibodies (aPLs), antinuclear antibodies (ANAs), and anti-sperm antibodies (ASA).Patients, Materials and Method: This prospective study was undertaken on ninety infertile women undergoing in vitro fertilization (IVF) programe. Their age was from 20years to 49 years. Blood specimens were collected from all women, on the day of egg pick up, and screened for all studied parameters by ELISA, and were statistically analyzed.Results: In the present study clinical pregnancy rate was 27.8%. And the present study showed a highly significant difference (P<0.01) in aPL (IgM, IgG) between patients and control group.The data in the present study, demonstrated a highly significant difference (P<0.01) in Antinuclear antibodies (ANAs) between the studied groups. Also a highly significant difference (P<0.01) in Antisperm antibodies (ASAs) between the studied groups.Conclusions: In vitro fertilization (IVF) failure, precisely failed embryo implantation, associated with produced auto-antibodies (anti-phospholipid antibodies, anti-sperm antibodies, and anti-nuclear antibodies), in the sera of the female.